From Material to Solution: Implementing Shape Memory Behavior of Thermoplastic Polymers in Commercial FEA Software for Structural Analysis - Fabian Neumann; Ferdinand Cerbe; Michael Sinapius (Journal of Manufacturing and Materials Processing)
The production of one-piece composite hollow profiles with undercuts presents significant challenges to conventional mold concepts. Mandrels made of thermoplastic shape-memory polymers could facilitate demolding and reduce tooling costs. To design molds in a commercial environment, it is critical to determine their behavior using off-the-shelf Finite Element Analysis (FEA) software. This paper investigates all of the necessary steps, from the material model generation, its implementation in commercial FEA software, to the simulation of shape-memory test specimens under unidirectional tensile loading with off-the-shelf FEA modules. The material investigated is PA6. Differential Scanning Calorimetry (DSC) is used to determine the glass transition, crystallization and melting temperatures of the material. The Dynamic Mechanical Analysis (DMA) is then used to determine the elastic modulus versus temperature and frequency. A viscoelastic material model is derived from DMA data. Parameters necessary for the implementation are derived by using fully open-source Python scripts. A unidirectional shape-memory tensile test simulation is performed and compared with the experimental data from a thermo-mechanical shape-memory test. The applied methods allow for the generation and implementation of a viscoelastic material model in commercial FEA software. The simulation shows good results in comparison with the thermo-mechanical shape-memory test. In conclusion, the straightforward “from material to solution” path presented allows us to model and simulate the shape memory behavior of viscoelastic polymers.